Financial Distress dan Faktor-Faktor Prediksinya - Elfreda Aplonia Lau (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2021)
Finance is a basic need for every company. No company started without finance and its sustainability also determined by financial factors. The importance of these financial factors for the sake of survival, a company needs to maintain healthy finances or prevent financial distress. This can be done if the company knows and understands financial distress and predict factors or factors that affect financial distress. This study is a library research that examines several empirical studies on financial distress and financial statements that are used to predict financial distress. The results of the study indicate that financial distress is a condition that indicates a company is at two extreme points starting from the company experiencing an inability to meet short-term financial obligations where the company is illiquid to the point of being insolvable and if not addressed immediately can experience bankruptcy. The results also show that to predict financial distress, logit regression analysis techniques, Altman Z-Score, Springate and Zmijewsky models and the Grover method can be used. Furthermore, this study shows that financial ratios can be used to predict financial distress either as a factor that has a significant positive effect or a significant negative effect, a significant positive effect or an insignificant negative effect. This is highly dependent on the posts forming the financial ratios used to predict the financial distress of a company as well as general factors, external factors and other internal factors. Keyword : Financial Distress, Financial Statements, Liquidity, Solvency, Profitability, Activity Ratio